The Effect of Water Column Resonance on the Spectra of Secondary Microseism P Waves - Meschede, M.; Stutzmann, E.; Farra, V.; Schimmel, Martin; Ardhuin, F. (Journal of Geophysical Research: Solid Earth, 2017)
We compile and analyze a data set of secondary microseismic P wave spectra that were observed by North American seismic arrays. Two distinct frequency bands, 0.13-0.15 Hz and 0.19-0.21 Hz, with enhanced P wave energy characterize the data set. Cluster analysis allows to classify the spectra and to associate typical spectral shapes with geographical regions: Low-frequency-dominated spectra (0.13-0.15 Hz) are mostly detected in shallower regions of the North Atlantic and the South Pacific, as well as along the Central and South American Pacific coast. High-frequency-dominated spectra (0.19-0.21 Hz) are mostly detected in deeper regions of the northwestern Pacific and the South Pacific. For a selected subset of high-quality sources, we compute synthetic spectra from an ocean wave hindcast. These synthetic spectra are able to reproduce amplitude and shape of the observed spectra, but only if P wave resonance in the water column at the source site is included in the model. Our data sets therefore indicate that the spectral peaks at 0.13-0.15 Hz and 0.19-0.21 Hz correspond to the first and second harmonics of P wave resonance in the water column that occur in shallower ocean depths (<3,000 m) and in the deep ocean (∼5,000 m), respectively. This article demonstrates the important effect of water column resonance on the amplitude and frequency of P waves that are generated by secondary microseisms and that the amplitude of high-quality sources can be predicted from ocean wave hindcasts within a factor of 0.4-6. ©2017. American Geophysical Union. All Rights Reserved. This article was funded through the ANR (Agence National de Recherche) project ANR-14-CE01-0012. Peer reviewed